Metode dan Jenis Pelarut untuk Ekstraksi Zerumbone dari Rimpang Zingiber zerumbet L. Smith: Kajian Pustaka: bahasa indonesia - Doloking, Haeria (Jurnal Farmasi UIN Alauddin Makassar, 2023)
The choice of extraction method and the solvent is a determining factor in the efficiency of extracting phytochemicals with unique and diverse physicochemical characteristics. This literature review aims to collect and examine information regarding the methods and solvents for extracting the zerumbone compound from the rhizome of Zingiber zerumbet (L) Smith. used and has been reported by various researchers. Data and information were collected using databases such as MDPI and Google Scholar. This study found various zerumbone extraction techniques, namely Microwave-Assisted Extraction, Supercritical-CO2, Subcritical Water Extraction, hydro distillation, soxhletation, reflux, and maceration. The solvents used were ethanol, methanol, ethyl acetate, n-hexane, chloroform, and water. The literature review shows that extraction efficiency with certain techniques depends on selecting the right solvent. Keywords: Microwave-Assisted Extraction, Supercritical-CO2, Subcritical Water Extraction, hydro distillation, Reflux